Design and Evaluation of Web-Based Dental Implant Registry (DIR) for Better Clinical Outcomes - Naemi, Roya; Jangi, Majid; Barikani, Hamid Reza; Shahmoradi, Leila (International Journal of Biomaterials, 2022)
Introduction. Identification of dental implant system in undocumented patients is a major challenge for dentists due to the vast variety of tools and technologies that are used in dental care. It also takes a long time to identify the type of connection or length and diameter of implant. To obtain accurate and timely information, it is necessary to have a Dental Implant Registry (DIR). In the present study, a DIR was designed, developed, and evaluated at the Dental Implant Research Center of Tehran University of Medical Sciences. Materials and Methods. This is an applied, developmental, and cross-sectional study that was conducted between 2018 and 2020. In the present study, after determining the objectives of DIR system, its conceptual model was designed by EDraw Max 7.9 software. Then, the registry was developed in Visual Studio 2018 environment with the C# programming language and, finally, it was evaluated by Nielsen’s ten principles of usability assessment. Results. After creating the registry, its data entry search and report functions were tested. Also, in the exploratory evaluation, the highest number of problems related to the principles of system clarity and compatibility between the system and real world was identified. Conclusion. The web-based DIR created in C# programming language has the ability to gather data, provide report with different access levels, and send text messages to patients for follow-up. This tool enables physicians to quickly identify the components of dental implant. The web-based DIR also provides support for health research, quality assessment, and dental performance assessment.